2016
DOI: 10.1159/000448714
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) Selectively Induces Relaxation and Modulates Endothelium-Dependent Dilation in Mesenteric Arteries of Salt-Fed Rats

Abstract: This study investigated the acute effects of angiotensin-(1-7) and AVE0991 on active tone and vasodilator responses to bradykinin and acetylcholine in isolated mesenteric arteries from Sprague-Dawley rats fed a high-salt (HS; 4% NaCl) versus a normal salt (NS; 0.4% NaCl) diet. Angiotensin-(1-7) and AVE0991 elicited relaxation, and angiotensin-(1-7) unmasked vasodilator responses to bradykinin in arteries from HS-fed rats. These effects of angiotensin-(1-7) and AVE0991 were inhibited by endothelium removal, A77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The vasodilation induced by Ang-(1-7) is mediated by NO production. 11 Thus, we investigated the effects of ageing on NO production in aortic rings from female mice. As shown in Figure 3 , elderly females present a significant decrease in NO as shown indirectly by DAF labelling.…”
Section: Resultsmentioning
confidence: 99%
“…The vasodilation induced by Ang-(1-7) is mediated by NO production. 11 Thus, we investigated the effects of ageing on NO production in aortic rings from female mice. As shown in Figure 3 , elderly females present a significant decrease in NO as shown indirectly by DAF labelling.…”
Section: Resultsmentioning
confidence: 99%
“…(1-7). A number of studies have shown the involvement of the AT2 receptor in the effects evoked by Ang-(1-7) (Bosnyak et al, 2011;Castro et al, 2005;Garcia-Garrote et al, 2019;Raffai & Lombard, 2016; Tesanovic, Vinh, Gaspari, Casley, & Widdop, 2010; Yousif et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, pre‐incubation the SCAPs with PD123319, an AT2 antagonist, attenuated the proliferative effect of Ang‐(1–7). A number of studies have shown the involvement of the AT2 receptor in the effects evoked by Ang‐(1–7) (Bosnyak et al, 2011; Castro et al, 2005; Garcia‐Garrote et al, 2019; Raffai & Lombard, 2016; Tesanovic, Vinh, Gaspari, Casley, & Widdop, 2010; Yousif et al, 2017). Although Ang‐(1–7) possess lower affinity for the AT2 receptor than Ang II, this heptapeptide presents substantial selectivity for AT2 (Bosnyak et al, 2011; Jones, Vinh, McCarthy, Gaspari, & Widdop, 2008; Walters, Gaspari, & Widdop, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to other authors, the administration of angiotensin-(1-7) caused severe vasodilatation in patients with hypertension [16], which may indirectly indicate a deficiency of this peptide. Several experimental models show the important role of angiotensin-(1-7) in preventing systemic hypertension [17,18] and vasodilation regulation [19,20]. In rats with hypertension, induction of diabetes caused a decrease in levels of angiotensin-(1-7), and increased levels prevented cardiovascular dysfunction, which develops in hypertension with diabetes [21].…”
Section: Discussionmentioning
confidence: 99%